Tax benefits for self-employed entrepreneurs in Algeria - Amina, Souyad; Kouadri, Abla (The International tax journal, 2025)
To encourage youth to access the entrepreneurial sector, and organizing the entrepreneurial activities of the modern technology; the Algerian legislator has introduced a legal status which has a pivotal role to exercise these activities; namely the independent contractor, according to the law N22-23 containing the Organic Law of the independent contractor. The legislator singled out independent contractor, with a set of privileges to encourage access to this system, The purpose of this study is therefore, to shed light on the on these various privileges.